Complications of total knee arthroplasty in patients with haemophilia compared with osteoarthritis and rheumatoid arthritis: A 20‐year single‐surgeon cohort. Issue 5 (27th July 2020) - Li, Zeng; Feng, Bin; Du, Yan; Wang, Yingjie; Bian, Yanyan; Weng, Xisheng
Abstract: Introduction: Patients with haemophilia are prone to haemophilic arthropathy (HA). For end‐stage HA, total knee arthroplasty (TKA) is an effective procedure. However, limited data were available regarding complications of TKA in HA patients. Aim: To provide comprehensive comparisons of TKA complications among patients with osteoarthritis (OA), rheumatoid arthritis (RA) or HA. Methods: The present study was a single‐surgeon cohort study including patients who underwent TKAs for OA, HA or RA from January 1997 to December 2017. The information of patients was extracted from medical records and follow‐up database. The primary outcome was complications. Potential risk factors of complications in HA patients were also evaluated. Results: A total of 1515 patients with 2083 TKAs were selected following the criteria. The overall complication rate in the HA group was 21.79%, which was much higher than the OA or RA group (7.08% and 8.70%, respectively, P < .05). The dominate complications were prosthetic loosening and wound dehiscence. For HA, more complications occurred in the period more than 1 year after TKA when compared with OA (33.33% vs 11.43%, P = .028). Among the potential risk factors, patients with haemophilia B and severe haemophilia had significantly higher complication rates ( P < .05 for both). Conclusion: When compared with OA or RA, HA patients had different characteristics on complications, including the higher complication rate, different complication distribution and later occurring time. In HA patients who underwent TKA, haemophilia B and severe haemophilia were risk factors of complications which should be paid more attention to.